Does Assertiveness and Friendliness Affect a Person's Satisfaction With Social Support? - Teh, H. P.; Teoh, H. J.; Pillay, S. K.; Kannan, K. (ANIMA Indonesian Psychological Journal, 2006)
The purpose of this study was to examine whether assertiveness and friendliness affect young adults' satisfaction with their social support. 93 young adults between the ages of 18 to 35 year-old participated in this study. The subjects were required to complete three sets of questionnaires consisting of "The Assertiveness Self-Report Inventory (ASRI)", "The Friendliness-Unfriendliness Scale (SACRAL)", and "The Sosial Support Questionnaire (SSQ)" The findings of this study have shown that assertiveness per say does not directly increase the quality of the young adult social support. However, it is the ability to engage in rewarding behaviors that increases the assertive young adults' satisfaction with her/his social support. Kajian ini bertujuan untuk menguji apakah tingkah laku asertif dan keramahan mempengaruhi kepuasan dukungan sosial di kalangan individu dewasa awal. Sembilan puluh tiga orang dewasa awal berusia di antara 18 hingga 35 tahun telah mengambil bagian dalam kajian ini. Subjek melengkapi 3 perangkat kuesioner yang terdiri atas "The Assertiveness Self-Report Inventory", "The Friendliness-Unfriendliness Scale" dan "The Social Support Scale". Temuan kajian menunjukkan tingkah laku asertif tidak meningkatkan kualitas dukungan sosial secara langsung di kalangan dewasa awal. Walau bagaimanapun, bertingkah laku yang menarik (rewarding behavior) dapat meningkatkan kepuasan dukungan sosial dikalangan individu dewasa awal yang asertif.